Faktor-Faktor Yang Mempengeruhi Kinerja Dosen Tetap Insuri Ponorogo - Nafi'ah .; Diyan Putri Ayu (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2018)
INSURI Ponorogo as a private Islamic higher institution under the auspices of the Nahdlatul Ulama Foundation (YAPERTINUKA) Ponorogo has problems related to the performance of lecturers. The performance of lecturers is closely related to financial factors and mengerial. The type of research used in this study is descriptive qualitative research. In this context, the informants in question are rector, dean and captain of INSURI Ponorogo, where they are also permanent lecturers. To get in-depth data is done by in-depth interview process. In-depth interviews were conducted by asking questions openly, allowing respondents to provide answers broadly. This data is then processed and analyzed by performance theory.The conclusions obtained from this study first, Factors that affect the performance of permanent lecturers INSURI in accordance with the opinion Mangkunegara in his book Human Resource Management Company is the ability factor and motivation factors. Second; Constraints faced in improving the performance of permanent lecturers INSURI is a constraint procedure that must be resolved. Third; Efforts to improve the performance of INSURI's permanent lecturers are participatory and transformative initiatives ranging from training, coaching and mentoring.